Multiscale attribution analysis for assessing effects of changing environment on runoff: case study of the Upstream Yangtze River in China - Yu Zhang (IWA Publishing, 2021)
Evaluating the changes in runoff and analyzing its attribution under the changing environment is of great significance to water resources management. In this study, eight hydrological stations at the outlets of tributaries of the Upstream Yangtze River are selected. Based on the observed runoff data from 1951 to 2013, the spatial-temporal characteristics in runoff change are identified from time series analysis. Our results show that runoff in the Upstream Yangtze River decreases significantly with a rate of −7.6 km3 per ten years in general. The most significant declines in runoff are observed in the mainstream, Minjiang River, Tuojiang River, and Jialing River, while slight increase in runoff is found in the source area of the Yangtze River. Furthermore, the effects on runoff change from climate change and human activities are evaluated using the Soil and Water Assessment Tool (SWAT) and modified Fixing-Changing (MFC) method at multiple scales. Our results suggest that the main contributions to runoff change are from climate change variabilities (70%), land use/cover change (LUCC, 10%), and other human influence (20%). When examined at different spatial and temporal scales, climate change always appears to be the main cause of runoff change, although its contribution decreases over time. HIGHLIGHTS Runoff in the Upstream Yangtze River decreased significantly.; Runoff decline is attributed to climate change, LUCC and other human influence.; Climate change appears to be the main cause of runoff change at different spatial and temporal scales.; Contribution of climate change decreases over time.; Precipitation and temperature are the main meteorological causes of runoff change.;